Splat! Another messy Sunday - Oliver, Lin (Oliver, Lin. Fantastic frame, 2018)
"Tiger and Luna return to the fantastic frame, and this time they enter the famous dotted world of Georges Seurat's painting, A Sunday Afternoon on the Island of La Grande Jatte. After arriving on the shore of the pleasant scene, they dash through Paris, get captured by police, and encounter one misadventure after another. And of course, Tiger and Luna must return to the real world to avoid getting trapped in the painting before time runs out!"--Provided by publisher.